Acute effects on the psychological perception of university students after participation in the “RegulACTION” workshop for the improvement of emotional health and promotion of an active lifestyle - Belando-Pedreño, Noelia; Mendoza-Castejón, Daniel; López, Carlos E. (Frontiers in Psychology, 2024)
Introduction Prospective research in Health Sciences and Sports Sciences warns of the need to design and implement educational program at the different stages of human development, that promote emotional competences, interpersonal competences, an adequate level of healthy physical activity as well as adherence to the Mediterranean diet and a more active lifestyle on a physical and social level. The main objective of the study was to design an intervention program on intra-and interpersonal competences together with emotional education, nutritional education and healthy physical activity, called ‘RegulACTION’. Methods The preliminary study sample consisted of 11 participants aged 21–28 years (M = 5.00, SD = 8.76) (8 female and 3 males) university students. An ad hoc questionnaire was elaborated to evaluate the participant’s perception of the usefulness of the ‘RegulACTION’ experience and a semi-structured interview of 5 questions to assess their perception, identification of their emotions, awareness of their cognitions, emotions and behaviors in the different areas of their lives. Results The descriptive results show that the participants are receptive to continuing training in the regulation of cognitions (thoughts) and emotions to increase their satisfaction in different areas of their lives. Regarding the qualitative results, the participants’ perception, collected verbatim, is that they feel the need to apply the knowledge about personal and social emotions, as well as healthy behavior in terms of nutrition and exercise, in their daily lives. Discussion The ‘RegulACTION’ program is designed based on the assessment of the prevalence of mental illness in the young adult and adult population, in line with the literature review in the area of knowledge of the theory of emotions, motivational theories and on the occasion of the development of a workshop organized.